Looking to the Future: Library Revitalization to Improve Literacy and Realize Student Nawacita at SDN Tlogotirto 1 - Ningrum, Putri Setiya; Sa'diyah, Halimah (International Journal of Elementary School Teacher, 2023)
The problem that is the focus of this research is the low level of literacy among students and the lack of complete library facilities at SDN Tlogotirto Elementary School. The study aims to revitalize the role of libraries to stimulate students' interest in literacy as part of efforts to support the achievement of the goals stated in Nawacita. This research uses descriptive qualitative methods. The subjects of this research were teachers, school principals and students. Data collection techniques use interviews, observation and documentation. Data analysis in this research includes reduction, data presentation, and conclusions. The research results showed that: 1) revitalization activities began with arranging and redecorating the library, sorting several books worth reading, labelling each book, and making a library visit logbook. Based on the classification, there were 514 student reading books, 86 encyclopedias, 150 general knowledge books, and 215 KTSP and K13 textbooks. 2) interest in literacy increases, with the average number of visits being 20 students every day. 3) the library can be an alternative solution to the classroom for studying. This research concludes that library revitalization has a significant positive impact on increasing students' interest in reading literacy. Libraries have great potential to become an adequate learning platform for students to achieve nawacita.